Reaksi Pasar Terhadap Pengumuman Pergantian CEO di Bursa Efek Indonesia - Agusnawan, I Kadek Diky; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 25 No 3 (2018)DO - 10.24843/EJA.2018.v25.i03.p30, 2018)
Announcement of CEO turnover indicates a change in company management in order to improve company performance. The purpose of this study is to test whether the capital market reacts to CEO turnover announcements. This study uses event study method and the sample was selected purposively. The research sample consisted of 79 companies listed in the IDX. Based on the results of the analysis it is found that there are no abnormal returns around the CEO turnover announcement. The results shows that there is no information content in the CEO turnover announcement. The results of this study is consistent with the research of Warner et al., (1998) and Setiawan (2008). The results of the study is not consistent with the research of Weisbach (1988), Kang and Shivdasani (1996), Derment-Ferere and Renneboog (2000), Bahtera (2017). Keywords : Chief executive officer, cumulative abnormal return, market reaction